Physiologic and Pharmacologic Effects of Glucocorticoids on Ion Transport across Rabbit Ileal Mucosa In Vitro - Sellin, Joseph H. (1981)
Physiologic and pharmacologic effects of glucocorticoids on ileal ion transport were examined in vitro. Tissues were obtained from the three following groups of rabbits: (a) normal; (b) glucocorticoid deficient, which were treated with aminoglutethimide (AG), 100 mg twice daily for 3 d, with a resulting marked reduction in urinary cortisol excretion but no decrease in urinary aldosterone; and (c) methylprednisolone-treated (MP), 40 mg daily for 2 d. Transileal NaCl fluxes were measured with radioisotopes under short-circuit conditions, and the net HCO(3) flux was assumed equal to that portion of the short-circuit current (I(sc)) not accounted for by Na and Cl. In NaCl Ringer's solution containing 25 mM HCO(3) (pH 7.4), normals absorbed both Na and Cl and secreted HCO(3); the I(sc) was greater in both AG and MP groups than in normals; in the AG group, no Na was absorbed, and Cl as well as HCO(3) was secreted; in the MP group, more Na was absorbed and more HCO(3) secreted than in normals. Addition of glucose to the luminal side caused similar increments in I(sc) in all three groups, suggesting similar rates of Na-coupled glucose absorption. Secretory response was assessed with a maximal secretory simulus (8-Br-cAMP) and also a submaximal, cGMP-related secretory stimulus (Escherichia coli heat-stable enterotoxin). After addition of 8-Br-cAMP, the rates of net Cl secretion were similar in all three groups, suggesting no effect of glucocorticoids on maximal secretory capacity. Because the AG group was already secreting Cl, however, the cAMP-induced change in net Cl flux was least in this group. After addition of heat-stable enterotoxin, there were similar changes in net Cl flux in all three groups. To examine specifically Cl-independent, electrogenic Na transport, we used a 10 mM HCO(3), Cl-free SO(4)-Ringer (ph 7.2) in which net Na absorption was previously shown to be equal to the I(sc). Under these conditions, I(sc) was greatest in the MP group and least in the AG group. In vitro addition of hydrocortisone, 50 μg/ml, to AG tissues had no effect on Cl fluxes or I(sc) over a 3.5-h period. No differences among groups were observed with respect to morphology, electrical resistance, or cGMP concentration. We conclude that (a) the effect of glucocorticoid deficiency is similar to that of a submaximal secretory stimulus in that Na absorption is inhibited and some Cl secretion develops; (b) electrogenic Na absorption is depressed in glucocorticoid deficiency and enhanced in glucocorticoid excess; (c) glucocorticoid excess increases HCO(3) secretion; and (d) glucocorticoid status does not affect maximal secretory capacity.